A Practical Approach for Optimal Power Distribution Among the West-to-East Power Transmission Channels with Minimized Losses - Gaihong CHENG; Qingchun ZHU; Jing YAN (Zhongguo dianli)
In order to reduce the power losses in power transmission from West to East, an optimal power distribution strategy with minimized losses is studied for the West-to-East power transmission channels based on both theoretical analysis and simulation calculations. The optimal power percentage of each DC transmission channel is determined with the principle of equal loss incremental rate. Based on the optimal power distribution among the DC transmission channels, the power system simulation tool is adopted to search for the reasonable power distribution between AC and the whole DC transmission channels. By introducing the step by step search strategy, the multivariable optimization problem involving power distribution among multiple transmission channels is converted to single variable optimization problem. Based on the line search strategy including advance and retreat algorithm and golden section algorithm, the optimal power distribution among transmission channels is thus determined through a small number of iterations. The proposed approach has been applied to West-to-East power transmission channels of CSG system, and the results demonstrate that the proposed approach is practical and easy to use, which can provide reference for dispatching and economic operation of power system.